Improving the effectiveness of road safety campaigns: Current and new practices - Tamara Hoekstra; Fred Wegman (IATSS Research, 2011)
The evaluation of campaigns aimed at improving road safety is still the exception rather than the rule. Because of this, ineffective campaigns and campaign techniques are allowed to continue to be utilised without question, while new methods of behaviour modification are often ignored. Therefore, the necessity and advantages of formally evaluating road safety campaign efforts are discussed. This article also describes the pros and cons of some of the more common campaign strategies and introduces a number of new methods that show a great deal of promise for the purpose of road safety campaigns. In order to infuse the field of road safety campaigning with such new insights into road user behaviour and behavioural modification, one should look beyond the confines of road safety campaign standards and learn from the knowledge gained in other disciplines such as economics and social psychology. These new insights are discussed in terms of their implications for the future of road safety campaigns.